Constructing a framework for the socioeconomic empowerment of women entrepreneurs. - Ahmad, Noorazlina; Baharudin, Mohamad Hanif; Ismail, Mohd Khairi (Journal of Islamic, Social, Economics and Development, 2025)
Women entrepreneurs face a variety of socioeconomic challenges, including limited access to capital, inadequate training, and lack of entrepreneurial knowledge. These barriers often hinder their ability to thrive and contribute meaningfully to their communities. This study aims to investigate the factors that influence business performance and subsequently build a comprehensive framework that supports the socioeconomic empowerment of women entrepreneurs, particularly those involved in the service sector. Using NVivo software, 26 indexed journal articles were analyzed to form a comprehensive framework. Marginalized groups such as single mothers, children, the elderly, and individuals with disabilities often face socioeconomic challenges. Reduced socioeconomic well-being poses challenges, particularly perpetuating poverty among affected individuals. Findings from this research are expected to guide policymakers, development agencies, and support institutions in designing targeted interventions that foster sustainable entrepreneurial growth and improve the overall quality of life for women entrepreneurs.